Infuences of Rice Husk Biochar (RHB) on Rice Growth Performance and Fertilizer Nitrogen Recovery up to Maximum Tillering Stage - Deniel Anak Sang; Rosenani Abu Bakar; Siti Hajar Ahmad; Khairudin Abdul Rahim (Center for Journal Management and Publication, 2018)
A pot study was carried out to investigate the effects of rice husk biochar addition on rice growth performance and fertilizer nitrogen recovery. The biochar effect was studied by using 15N labelled fertilizer urea (10 atom% 15N), as isotopic tracer, until maximum tillering stage (75 days after sowing). Rice husk biochar (RHB) was applied at rates of 0, 5, 10 and 20 Mg ha-1 and laid in randomized complete block design with four replications. The result showed that biochar application significantly improved soil chemical properties (pH, total C, total N, and available P) compared to control treatment. Biochar addition increased number of tiller and root dry matter weight up to 4% and 35%, respectively, compared to un-amended pot. Likewise, application of biochar significantly increased N, P and K uptake by 3%, 19% and 33%, respectively, as compared to the nutrient uptake from the control treatment. Biochar treatment had no significant impact on fertilizer nitrogen recovery in aboveground biomass, in the range of 41% and 42%, in comparison to the control. However, nitrogen fertilizer recovery in soil significantly increased by 47% over the control at application rate of 20 Mg ha-1 RHB. Â Increased fertilizer N recovery in soil possibly reduced N losses to the environment from volatilization and denitrification processes. Total 15N fertilizer recovery also found increase at highest application of RHB biochar with an increment of 16%. In general, addition of biochar appeared to enhance crop growth performance but its effect on fertilizer N recovery in plant requires further study up to maturity of rice plant.